The effects of noticing training on Malay ESL learners’ use of past time forms in writing - Lotfie, Maskanah Mohammad; Abd Samad, Arshad (2008)
Academic writing is a productive skill that is especially crucial at the tertiary level. At Malaysian institutions where English is the medium of instruction, not only does a student need to write convincingly but he also has to do so effectively. This would mean writing with some sound knowledge of the content area, as well as ensuring the coherence of ideas and accuracy of grammatical structures. That the latter is of great importance is succinctly pointed out by Muncie (2002) who mentions that “grammar is just as important an instrument of communication as content, and a text cannot be written cohesively without attention being paid to how meaning is being expressed through the grammar” (p. 183). Similarly, Ferris (2002) asserts that students’ morphological and syntactic accuracy is important because inaccuracy may interfere with the comprehensibility of their written message. Ensuring grammatical accuracy is therefore an exceptionally important element of academic writing as it facilitates successful communication. Many institutions of higher learning in Malaysia such as Universiti Teknologi MARA, Kolej Ugama Sultan Zainal Abidin, and the International Islamic University Malaysia (IIUM), use English as the medium of instruction. Nevertheless, ESL instructors at these institutions are continuously facing the problem of students’ written work seldom demonstrating grammatical improvement. This phenomenon persists even after semesters of intensive training at the post-secondary levels, in addition to the years of learning English in primary and secondary schools. Even though the most commonly used English language structures are taught to students, their written work tends to be peppered with numerous recurring grammar errors. This problem can seriously jeopardise the quality of their written output and compromise the effectiveness of their written communication. A student may have to compose an essay for a test or an assignment on his major-related work and may have all the relevant content that can make his paper a high-scoring one, but undue grammatical problems may result in incomprehensible or unclear written work thus lowering his grade.